Suppression of host nocifensive behavior by parasitoid wasp venom - Rana, Amit; Emanuel, Stav; Adams, Michael E.; Libersat, Frederic (Frontiers in Physiology, 2022)
The parasitoid wasp Ampulex compressa envenomates the brain of its host the American cockroach (Periplaneta americana), thereby making it a behaviorally compliant food supply for its offspring. The target of venom injection is a locomotory command center in the brain called the central complex. In this study, we investigate why stung cockroaches do not respond to injuries incurred during the manipulation process by the wasp. In particular, we examine how envenomation compromises nociceptive signaling pathways in the host. Noxious stimuli applied to the cuticle of stung cockroaches fail to evoke escape responses, even though nociceptive interneurons projecting to the brain respond normally. Hence, while nociceptive signals are carried forward to the brain, they fail to trigger robust nocifensive behavior. Electrophysiological recordings from the central complex of stung animals demonstrate decreases in peak firing rate, total firing, and duration of noxious-evoked activity. The single parameter best correlated with altered noxious-evoked behavioral responses of stung cockroaches is reduced duration of the evoked response in the central complex. Our findings demonstrate how the reproductive strategy of a parasitoid wasp is served by venom-mediated elimination of aversive, nocifensive behavior in its host.